Innovative techniques in the planning and financing of public transportation projects. (Research results digest (Transit Cooperative Research Program), 2006)
"This TCRP digest summarizes the mission performed October 20-November 5, 2005, under TCRP Project J-3, 'International Transit Studies Program.' This digest includes transportation information on the cities and facilities visited. This digest was perpared by the staff of the Eno Transportation Foundation and is based on reports filed by the mission participants."--p. 1.